Vous êtes sur la page 1sur 42

# EJERCICIO N1

1.

Y =x 3 +4 x2 x
dy d 3 d
d
= ( x ) + ( 4 x 2 ) ( x )
dx dx
dx
dx
dy
d
=3 x 31 +4 ( x 2 ) 1
dx
dx
dy
=3 x 2 +4 ( 2 x 21 )1
dx
dy
=3 x 2 +8 x1
dx

2.

Y =8 x 4 3 x2 +6
dy d
d
d
4
2
= (8 x ) (3 x )+ ( 6 )
dx dx
dx
dx
dy
d
d
=8 ( x 4 )3 ( x 2 ) +0
dx
dx
dx
dy
=8 ( 4 x 4 1) 3 ( 2 x21 ) +0
dx
dy
=32 x 36 x +0
dx

3.

Y =5 x 10 x +2 x +5 x4

dy d
d
d
d
d
4
3
2
= ( 5 x ) ( 10 x )+ ( 2 x ) + ( 5 x ) ( 4)
dx dx
dx
dx
dx
dx
dy
d
d
d
d
=5 ( x 4 )10 ( x 3 )+ 2 ( x 2 ) +5 ( x ) 0
dx
dx
dx
dx
dx
dy
=5 ( 4 x 4 1 ) 10 ( 3 x 31 ) +2 ( 2 x21 ) +5 ( 1 )0
dx
dy
3
2
=20 x 30 x +4 x +50
dx

4.

Y =8 x + x x +7 x 15
dy d
d 3 d 2 d
4
1
= ( 8 x ) + ( x ) ( x ) + ( 7 x ) 15
dx dx
dx
dx
dx
dy
d 4
d 1
3 1
21
=8 ( x ) +3 x (2 x
)+7 ( x )0
dx
dx
dx
dy
=8 ( 4 x 4 1) + 3 x 2 +2 x 3 +7 (1 x 11 )0
dx
dy
=32 x 3 +3 x2 +2 x37 x20
dx

5.

Y =6 x 4 x + 3 x +6
dy d
d
d
d
= ( 6 x3 ) ( 4 x 2 ) + ( 3 x )+ (6)
dx dx
dx
dx
dx

dy
d 3
d 2
d
=6 ( x ) 4 ( x ) +3 ( x )+ 0
dx
dx
dx
dx
dy
=6 (3 x31 )4 (2 x 21 ) +3 ( 1 )+ 0
dx
dy
=18 x4 +8 x3+ 3+0
dx

6.

Y =x 2 + x 3 +6 x +3
x
1
3

( )

1 d
d
d
( )+
x + 6 x+ 3
2 dx
dx
dx
dy d
=
dx dx
1

dy 1 2 1 1 13 1
d
= x + x +6 x+ 0
dx 2
3
dx
1

dy 1 2 1 23
= x + x +6 (1)+0
dx 2
3
1

dy 1 2 1 23
= x + x +6+ 0
dx 2
3

7.

Y = 3 x +4 x3 x

1
2

dy d 3
d
d
= ( x)+ (4 x) (3 x 2 )
dx dx
dx
dx
1

dy d 3
d
d
= ( x )+4 (x 2 )3 ( x 2 )
dx dx
dx
dx
1

dy 1 3 1
1 1
1
= x +4 ( x 2 )3(
x
dx 3
2
2
2

3
2

1
4

1
2

1
3

dy 1 3 4 2 3
= x + x + x
dx 3
2
2

Y =x + 4 x 9 x

8.

1
1
2

( )+ dxd ( 4 x ) dxd (9 x

dy d
=
x
dx dx
dy 1
=
x
dx 4

1
4

1
1
4

1
2

( )9 dxd (x

d
+4
x
dx

dy 1 1 4
1
=
x +4
x
dx 4
2
1

1
3

1
2

1
1
2

1
3

1 13 1
9(
x
)
3
1

dy 1 1 4 4 1 2 9 1 3
=
x x + x
dx 4
2
3

9.

Y=

6 3
+ 3
2
x x

Y =6 x2 +3 x3

dy d
d
2
3
= (6 x )+ (3 x )
dx dx
dx
dy
d
d
=6 ( x2)+3 ( x3)
dx
dx
dx
dy
=6(2 x 21)+3 (3 x31)
dx
dy
3
4
=12 x 9 x
dx

10.

Y=

8 5 6
5 + 2 =Y =8 x 4 5 x5 +6 x 2
4
x x x

dy d
d
d
4
5
2
= ( 8 x ) ( 5 x ) + (6 x )
dx dx
dx
dx
dy
d 4
d 5
d 2
=8 ( x )5 ( x ) +6 (x )
dx
dx
dx
dx
dy
=8 (4 x41 )5 ( 5 x51) + 6(2 x 21)
dx
dy
=32 x5+25 x612 x3
dx

EJERCICIO N2
1.

Y =x x + 4 x 6 x7
dy d 4 d 3 d
d
d
= ( x ) (x )+ (4 x 2) (6 x) 7
dx dx
dx
dx
dx
dx
dy
d 2
d
4 1
31
=4 x 3 x +4 ( x )6 (x)0
dx
dx
dx
dy
3
2
21
=4 x 3 x + 4 (2 x )6(1)0
dx
dy
=4 x 33 x 2+ 8 x60
dx

2.

1
1
14
Y = x x + x x
9
8
7
dy d 1 9
d 1 8 d 14 7
d
=
x
x +
x (x )
dx d x 9
dx 8
dx 7
dx

( ) ( ) ( )

dy 1 d 9 1 d 8 14 d 7
=
( x )
( x )+
( x ) 1
dx 9 dx
8 dx
7 dx
dy 1
1
14
91
81
71
= ( 9 x ) ( 8 x ) + ( 7 x ) 1
dx 9
8
7
dy 9 8 8 7 98 6
= x x + x 1
dx 9
8
7
dy
=1 x 81 x 7+ 14 x6 1
dx

3.

3
6
7
Y = x + x x 10 x +4
4
8
9
8

( ) ( ) ( )

dy d 3
d 6
d 7
d
d
=
x +
x
x ( 10 x ) + ( 4 )
dx dx 4
dx 8
dx 9
dx
dx
dy 3 d 8 6 d 7 7 d 6
=
( x )+
( x )
( x )10 d ( x )+ 0
dx 4 dx
8 dx
9 dx
dx
dy 3
6
7
= ( 8 x 81 ) + ( 7 x71 ) ( 6 x 61 )10 ( 1 )
dx 4
8
9
dy 24 7 42 6 42 5
= x + x x 10
dx 4
8
9
dy
2 6
6 5
7
=6 x +5 x 4 x 10
dx
8
9

4.

3
2
3
Y = x x x + 4 x 4 +6 x
9
16
5
dy d 3 9
d 2 6
d 3 5 d ( 4) d
=
x
x
x +
4 x + (6 x )
dx dx 9
dx 16
dx 5
dx
dx

( ) ( ) ( )

dy 3 d 9 2 d 6 3 d 5
=
( x )
( x )
( x ) + 4 d ( x 4 ) +6 d ( x )
dx 9 dx
16 dx
5 dx
dx
dx
dy 3
2
3
91
61
51
41
= ( 9 x ) ( 6 x ) ( 5 x ) + 4 ( 4 x ) +6 ( 1 )
dx 9
16
5
dy 27 8 12 5 15 4
3
= x x x +16 x + 6
dx 9
16
5
dy
12
=3 x 8 x5 3 x 4+ 16 x3 +6
dx
16

5.

2
6
7
Y = x 4 x 3+ x2 +6 x +4
4
3
2
dy d 2 4
d 6 3 d 7 2 d
d
=
x
x +
x + ( 6 x ) + ( 4)
dx dx 4
dx 3
dx 2
dx
dx

( ) ( ) ( )

dy 2 d 4 6 d 3 7 d 2
=
( x )
( x )+
( x ) +6 d ( x )+ 0
dx 4 dx
3 dx
2 dx
dx

dy 2
6
7
= ( 4 x 3 ) ( 3 x2 ) + ( 2 x ) +6 ( 1 ) +0
dx 4
3
2
dy 8 3 18 2 14
= x x + x +6
dx 4
3
2
dy
=2 x 36 x 2 +7 x+ 6
dx

6.

8
18
14
Y = x 3 x 2 + x +6 x
4
3
2
dy d 8 3
d 18 2 d 14
d
=
x
x +
x + (6 x)
dx dx 4
dx 3
dx 2
dx

( ) ( ) ( )

dy 8 d 3 18 d 2 14 d
d
=
( x )
( x )+
( x ) +6 ( x )
dx 4 dx
3 dx
2 dx
dx
dy 8
18
14
= ( 3 x 2 ) ( 2 x ) + ( 1 ) +6 ( 1 )
dx 4
3
2
dy 24 2 36
14
= x x+ +6
dx 4
3
2
dy
=6 x2 12 x +7+6
dx

EJERCICIO N3
1

1.

Y =5 x 4 3 x 3 + x 2 6
1

( )

dy d ( 4 ) d ( 3 ) d 2
d
=
5x
3x +
x (6)
dx dx
dx
dx
dx
1

dy
d
d
1 1
=5 ( x 4 )3 ( x3 ) + x 2 0
dx
dx
dx
2
1

dy
4 1
31
=5 ( 4 x ) 3 (3 x
) + 1 x 2 0
dx
2
1

dy
1
=20 x 3 +9 x4 + x 2 0
dx
2

2.

Y =10 x 95 x 8 +4 x + 3 x

dy d
d
d
d 3
9
8
= ( 10 x ) ( 5 x ) + ( 4 x )+ ( x )
dx dx
dx
dx
dx
1

( )

dy
d 9
d 8
d
d 3
=10 ( x ) 5 ( x ) + 4 ( x )+
x
dx
dx
dx
dx
dx
1

dy
1 1
=10 ( 9 x 91 ) 5 ( 8 x8 1 ) + 4 ( 1 ) + x 3
dx
3
dy
1
=90 x8 40 x 7 +4 + x
dx
3

3.

Y =7 x 4 8 x 3+

2
3

5 2
2
3
x x

dy d
d
d 5
d 2
= ( 7 x 4 ) ( 8 x 3 ) +

3
dx dx
dx
dx x
dx x 2

( ) ( )

dy
d
d
d
d
=7 ( x 4 )8 ( x 3 ) + ( 5 x3) ( 2 x2 )
dx
dx
dx
dx
dx
dy
d
d
=7 ( 4 x 4 1 ) 8 ( 3 x 31) +5 ( x3 )2 ( x2 )
dx
dx
dx
dy
=28 x 324 x2 +5 (3 x3 1 ) 2 ( 2 x21 )
dx
dy
=28 x 324 x2 15 x 4 + 4 x3
dx

4.

Y =3 x + 4 x 2 x a

dy d
d
d
d
= ( 3 x 4 ) + ( 4 x 3 ) ( 2 x 2 ) ( a )
dx dx
dx
dx
dx
dy
d
d
d
=3 ( x 4 ) +4 ( x 3 ) 2 ( x 2 )0
dx
dx
dx
dx
dy
=3 ( 4 x 4 1 ) + 4 ( 3 x 31 )2 ( 2 x 21 )0
dx
dy
=12 x 3 +12 x 24 x0
dx

5.

Y =15 x 5 +6 x 42 x 34 x3 + 4
dy d
d
d
d
d
5
4
3
3
= ( 15 x ) + ( 6 x ) ( 2 x ) ( 4 x ) + ( 4 )
dx dx
dx
dx
dx
dx
dy
d
d
d
d
=15 ( x 5 ) +6 ( x 4 ) 2 ( x 3 ) 4 ( x 3 ) +0
dx
dx
dx
dx
dx
dy
=15 ( 5 x 51 ) +6 ( 4 x 41 )2 ( 3 x 31) 4 (3 x 31 ) +0
dx
dy
=75 x 4 + 24 x3 6 x 2+12 x4 +0
dx

6.

Y =x 2 + x 3 x 4

( )

( )

( )

dy d 2 d 3
d 4
=
x +
x
x
dx dx
dx
dx
1

dy 1 2 1 1 3 1 1 14 1
= x + x x
dx 2
3
4
dy 1
= x
dx 2

7.

1
2

1
1 3
+ x3 x4
3
4

Y =(x+ 6)

dy
41 d
=4 (x +6)
(x+ 6)
dx
dx

dy
d
d
=4 ( x+ 6)3
( x ) + (6)
dx
dx
dx
dy
3
=4 (x+ 6) (1+ 0)
dx
dy
=4 (x+ 6)3 (1)
dx
dy
=4 (x+ 6)3
dx

8.

4
2+

1
Y=
x

4
2+
3
dy
=
dx
x

4
2+
3
dy
=
dx
x

4
2+
3
dy
=
dx

4
2+
3
dy
=
dx
x

4
2+
6 x
dy
=
dx
x

4
2+

dy 6 x
=

dx

9.

9
3 x2 +

3
2
Y = 3 x + 9=
1

d
( 3 x2 +9 )
dx
dy 1
=
dx 3

3 x2 +9 3

3 x2 +9

2
3

d
( 3 x 2 )+ d ( 9 )
dx
dx
dy 1
=
dx 3

2
3

d 2
( x )+ 0
dx
dy 1
=
dx 3

3 x2 +9

3 x2 +9 3 [ 3 ( 2 x21 ) ]
dy 1
=
dx 3
2

3 x2 +9 3 ( 6 x )
dy 1
=
dx 3
2

2
3

3 x +9
dy 6 x
=

dx 3
2

3 x 2 +9 3

2
3

3 x +9 =

2x

dy
=2 x
dx
2

3 x +9

dy 2 x
=
dx

EJERCICIO N4

x 4 +10 3
Y =

1.

x 4 +10 31

d 4
( x +10 )
dx

dy
=3
dx
4

x +10

d 4 d
( x ) + (10)
dx
dx
dy
=3
dx

x 4 +10 2 [ 4 x 41 +0 ]
dy
=3
dx

x 4 +10 2 [ 4 x 3 ]
dy
=3
dx
4

x +10
dy
=12 x 3
dx

3 x5 +6 5
Y =

2.

3 x5 +6 51

d
(3 x 5 +6)
dx

dy
=5
dx
5

3 x +6

d
( 3 x5 ) + d ( 6 )
dx
dx
dy
=5
dx

3 x +6 3

d 5
( x )+ 0
dx

dy
=5
dx

3 x5 +6 4 [ 3 ( 5 x 51 ) ]
dy
=5
dx
3 x5 +6 4 ( 15 x 4 )
dy
=5
dx

3 x +6
dy
=75 x 4
dx

8 x 3+7 4
Y =

3.

8x
( 3+ 7)
d
8 x 3+7 41
dx
dy
=4
dx
3

8 x +7

d
( 8 x3)+ d ( 7)
dx
dx
dy
=4
dx

8 x +7 8

d 3
( x ) +0
dx

dy
=4
dx

8 x +7 [ 8 ( 3 x
dy
=4
dx
3

31

8 x +7 (24 x )
dy
=4
dx

)]

8 x +7
dy
=96 x 2
dx

4.

x+1

x+1

1
Y=
x+1

dy
=3
dx
x+1

dy
=3
dx
x+1

dy
=3
dx

x+1

dy
=3
dx

4 x 1

3
7
4 x 1

1
Y=

5.

7 1

4 x 1

d
3
(4 x 1)
dx

dy
=7
dx
8

4 x 1

d
( 4 x 3 ) d ( 1 )
dx
dx
dy
=7
dx

4 x 1

d 3
( x )0
dx

dy
=7
dx

4 x 31 8 [ 4 ( 3 x3 1 ) ]
dy
=7
dx
4 x 31 8 ( 12 x2 )
dy
=7
dx

4 x 1
dy
=84 x2
dx

10

3 x 1

5
3 x 110

1
Y=

6.

3 x5 1101

d
( 3 x 51 )
dx

dy
=10
dx
3 x5 111

d
( 3 x 5 ) d (1 )
dx
dx

dy
=10
dx

3 x5 111 3

d 5
( x ) 0
dx

dy
=10
dx
3 x 1 [ 3 ( 5 x
dy
=10
dx
5

11

51

)]

3 x5 111 ( 1 5 x 4 )
dy
=10
dx
5

11

3 x 1
dy
=150 x 4
dx

x+ 1

1
2

7.

x +1 2

1
1
Y=
=
x+1
1
1
2

d
( x +1 )
dx
dy 1
=

dx 2

x+ 1

x+ 1

3
2

d
d
( x )+ ( 1 )
dx
dx
dy 1
=

dx 2

3
2

x+ 1 [ 1+ 0 ]
dy 1
=

dx 2
3

x+ 1 2 ( 1 )
dy 1
=

dx 2

x+ 1 2
dy 1
=

dx 2

x +9

1
3

x 3 +9 3

1
1
Y= 3 3 =
x +9

8.

1
1
3

d 3
( x + 9)
dx
dy 1
=

dx 3

x +9

d 3 d
( x )+ ( 9)
dx
dx
dy 1
=

dx 3

x 3+ 9 3

x 3+ 9 3 [ 3 x 31 +0 ]
dy 1
=

dx 3

x 3+ 9 3 (3 x 2)
dy 1
=

dx 3
4

x3 + 9 3
dy 3 x2
=

dx
3
4

x 3 +9 3
dy
=x 2
dx

x 4 + 16 2
Y = x 4 +16=

9.

d 4
(x +16)
dx
dy 1
=
dx 2

x 4 +16 2

x 4 +16 2

d 4 d
( x ) + ( 16 )
dx
dx
dy 1
=
dx 2
41

x +16 2 [ 4 x
dy 1
=
dx 2
1

x 4 +16 2 (4 x3 )
dy 1
=
dx 2

+0 ]

x 4 + 16 2
dy 4 x 3
=

dx
2

x 21 4
4
Y = x 21=

10.

1
1
4

d 2
( x 1 )
dx
dy 1
=
dx 4

x 1

x 21

3
4

d 2 d
( x ) ( 1 )
dx
dx
dy 1
=
dx 4

x 21 4 [ 2 x210 ]
dy 1
=
dx 4
2

3
4

3
4

x 1 ( 2 x )
dy 1
=
dx 4

x 1
dy 2 x
=
dx 4

EJERCICIO N5
x 31 4
Y =x

1.

d
x
dx
x 31 4 +
dy
d
=x
dx
dx

x 31 4

d 3
( x 1 )
dx
x3 1 4 ( 1 )
4 +
dy
=x
dx

x 31 3

x 1 ( 3 x 0 )
3
4
x 1 ( 1 )
4 +
dy
=x
dx
3
4
x 1 ( 1 )
x3 1 3+
dy
3
=12 x
dx

2.

Y =( x +1 ) ( x 1 )
dy
d
d
=( x +1 ) ( x1 )+ ( x1 ) ( x+1)
dx
dx
dx
dy
=( x +1 ) ( 10 )+ ( x1 )( 1+0 )
dx
dy
=( x +1 ) ( 1 )+ ( x1 )( 1 )
dx
dy
=( x +1 ) + ( x1 )
dx

3.

Y =( x 2 +4 ) ( x 31 )
dy
d
d
=( x 2+ 4 ) ( x 31 ) + ( x 31 ) ( x 2 +4 )
dx
dx
dx
dy
=( x 2+ 4 ) ( 3 x 20 )+ ( x 31 ) ( 2 x +0 )
dx
dy
=3 x 2 ( x 2+ 4 ) + 2 x ( x3 1 )
dx
dy
=( 3 x 4+ 12 x 2 ) + ( 2 x 42 x )
dx

4.

Y =x 2 ( x3 +2 )

x
( 2)
dy
2 d
( x3 +2 ) + ( x3 +2 ) d
=x
dx
dx
dx

dy 2
=x ( 3 x 2+0 ) + ( x 3+ 2 ) ( 2 x )
dx
dy
4
4
=3 x + ( 2 x + 4 x )
dx

5.

Y = x ( x +9 )
1

dy
=x 2 ( x +9)
dx
x
1
( )
2

dy
d
d
=x 2
( x +9 )+( x +9)
dx
dx
dx
1
x
2
1
(
)
2
1

dy
=x 2 ( 1+ 0 ) +( x +9)
dx
1

dy
1
9
=x 2 + x 2 +
dx
2
2

6.

Y =( x 325 ) ( x +1 )
dy
d
d
=( x3 25 ) ( x+1 ) + ( x +1 ) ( x 325 )
dx
dx
dx
dy
=( x3 25 ) ( 1+0 ) + ( x +1 ) ( 3 x 20 )
dx
dy
=( x3 25 ) + ( 3 x 3 +3 x2 )
dx

7.

x 325 2
Y =x 2
d 2
(x )
dx
x 325 2 +
dy 2 d
=x

dx
dx

x 325 2

x 3 25 2 (2 x )
dy 2
d 3
3
=x 2(x 25) (x 25) +
dx
dx

x 25

dy 2
=x [ 2( x 325)(3 x 20) ] +2 x
dx

x 25

dy
=6 x 4 ( x 3 25 ) +2 x
dx

8.

6 x +1

Y =3 x 3
6 x +1

6 x +1

dy
d
=3 x 3
dx
dx
d
(6 x +1)
dx
6 x +1

4 +
dy
=3 x 3
dx

6 x+ 13

6 x+ 1 (6(1)+ 0)
6 x +1

4 +
dy
3
=3 x
dx

6 x+ 1 (6)
6 x +1

4 +
dy
3
=3 x
dx
6 x +1

3
6 x +1 +
dy
3
=72 x
dx

x+ 1
9.

1
2

1
2

x +1
Y = x +1 x +1=
1
2

x+1
1
d
x+ 1 2

dx
1
2

x +1 +
1
d
x+ 1 2

dx
dy
=
dx

x+ 1 2
1

x+ 1 2
1

1
1

x+1 2
1
+
2
1
2

x+1
dy
=
dx

x+ 1
x+ 1
1

1
2
1
2

x+ 1 2
1
+
2
1

x+ 1 2
dy
=
dx
1
2

x +1

1
2

x +1
1
1
x+ 1 2 +
2
1
2

x +1
dy 1
=
dx 2

10.

4 x+1 3
Y =( 5 x +1 )

d
(5 x +1 )
dx
4 x +1 3 +
dy
d
=( 5 x +1 )
dx
dx
3

4 x +1

4 x +1
4 x +1 3 [ 5 (1)+0 ]
3 +
dy
=( 5 x+1 )
dx
4 x+ 1 2
4 x +1 3 (5)
3 +
dy
=( 5 x +1 )
dx
3

4 x+1 (5)
4 x +1 2+
dy
=15 x +3
dx

EJERCICIO N6

1.

Y=

(x+ 9)
( x9)
x9

dy
=
dx

( x9 )

d
d
( x +9 ) ( x +9 ) ( x9)
dx
dx

x9

dy ( x9 )( 1+0 )( x+ 9 ) (10)
=

dx
x9 2

dy x9x9
=

dx
x 9 2

dy 18
=
dx

2.

Y=

x 24
x 2+ 4
x
x
x
x 2 +4 2

d 2
( x + 4)
dx

( 24 )
( 24)
( 2+ 4)

dx

dy
=
dx

x
x
2
x + 4 2

( 24)(2 x+ 0)
( 2+4 )(2 x0)

dy
=
dx
2

x +4

3
3
dy 2 x + 8 x 2 x +8 x
=

dx

x +4

dy 16 x
=
dx

3.

Y=

x 125
2
x
x
( 2)2

dy
=
dx

( x 2 ) d ( x3 125 )( x3 125 ) d ( x2 )
dx

dx

x
( 2)2
2
2
3
dy ( x ) ( 3 x 0 ) ( x 125 ) ( 2 x )
=

dx
x
2
( 2)
4
4
dy 3 x 2 x 250 x
=

dx
x
( 2)2
dy x 4 250 x
=

dx

4.

Y=

dy
=
dx

4x
x+ 1

( x +1 )

d
( 4 x 2 )(4 x 2 ) d ( x+ 1 )
dx
dx
2
( x+1 )

2
dy ( x +1 ) 8 x(4 x ) (1+ 0 )
=
dx
( x+1 )2

dy 8 x +8 x4 x
=
dx
( x +1 )2

dy 4 x 2+ 8 x
=
dx ( x+ 1 )2

5.

4 x 41
Y= 3
x +2
x
x
x
( 3+ 2)2

( 3+2)

d ( 4 ) ( 4 ) d ( 3+2)
4 x 1 4 x 1

dx
dx

dy
=
dx

x
3x
x
( 3+ 2)2
( 3+2) ( 16 x 30 )( 4 x 4 1 )

dy
=
dx

( 2+0)

x
( 3+2)2
dy 16 x 6 +32 x 312 x 6 +3 x2
=

dx
x
2
( 3+2)
6
3
2
dy 4 x + 32 x +3 x
=

dx

6.

Y=

dy
=
dx

x
x+ 6

( x +6 )

d
d
( x ) ( x ) (x +6)
dx
dx
2
( x +6 )

dy ( x +6 ) ( 1 )( x ) (1+0)
=
dx
( x +6 )2
dy x +6x
=
dx ( x+ 6 )2
dy
6
=
dx ( x +6 )2

7.

Y=

dy
=
dx

x +a
xa

( xa )

d 3
( x +a ) ( x 3 +a ) d (x a)
dx
dx
2
( xa)

2
3
dy ( xa ) ( 3 x +0 ) ( x + a ) (10)
=
dx
( xa)2

dy 3 x 53 axx 3 +a
=
dx
(xa)2

8.

Y=

dy
=
dx

x3
x 24

( x 24 ) d ( x 3 )(x 3) d (x 24)
dx

dx

( x 4 )

2
2
3
dy ( x 4 ) 3 x (x )(2 x0)
=
dx
(x 24)2

dy 3 x 412 x 22 x 4
=
2
2
dx
( x 4)
dy x 4 12 x 2
=
dx ( x 24 )2

9.

Y=

dy
=
dx

x+ 5
x3

( x 3 ) d ( x+5 )( x+ 5 ) d ( x 3 )
dx

dx

3 2

(x )

3
2
dy ( x ) ( 1+ 0 ) ( x +5 ) ( 3 x )
=
2
dx
( x3 )

dy x 33 x 315 x 2
=
2
dx
( x3 )

x
10. Y = x+1
1

x+ 1

1
2

x +1 2

x+1 2

d 2
( x ) ( x 2 ) d
dx
dx

dy
=
dx

x +1 2
1

x +1 2

x+ 1 2 ( 2 x )( x 2 )

dy
=
dx
1
2

x +1

x+1 2

1
1 2
2
x+ 1 x
2
(2 x )
dy
=
dx

( )